The Application of Genetics to Forestry - Varma, J. C. (Indian Forester, 1950)
The possibility of forest tree improvement through genetical methods is beyond any contradiction. The use of breeding techniques in tree improvement is of recent origin, though provenance studies on the adaptability of races to particular localities date back to the end of the last century. More precise methods in selection have been taken up and adequate testing methods evolved. Hybridization and the employment of heterosis have already yielded valuable results and the difficulty of time involved therein has been overcome by the induction of early flowering and fruiting, through such techniques as strangulation, grafting, root pruning, etc. The production of hybrid seeds on a commercial scale can be brought into the scope of economic possibility through cleverly designed Tree Seed Plantations. The rapid progress achieved in the improvement of agricultural crops through cytological research and the use of polyploidy has had its effect on forest geneticists who have furnished evidences of the use and value of such techniques when applied to forest tree improvement.